THE ROLE OF THE INDONESIAN STEEL INDUSTRY IN SUPPORTING THE INDONESIA DEFENSE INDUSTRY - Irdam Ahmad; Mirad Fahri (Jurnal Pertahanan: Media Informasi ttg Kajian & Strategi Pertahanan yang Mengedepankan Identity, Nasionalism & Integrity, 2021)
The steel industry plays a pivotal role in driving the economy of a country because its production is used not only as raw material by many downstream industries, such as defense, machinery, and automotive industries, but also for infrastructure development, such as roads, bridges, and buildings. This study aims to analyze the role of the Indonesian steel industry in supporting the Indonesian defense industry and analyze the steel industry value chain, the competitiveness of domestic steel products against imported steel, and the relationship between the steel industry and the defense industry. This research used sequential mixed research methods, using raw data of manufacturing survey by Central Statistics Agency (BPS). Descriptive analysis, such as geometric growth rate, competitiveness analysis using the Trade Specialization Index (ISP), and analysis of the linkage between upstream and downstream steel industries using the 2010 Input-Output Table, employed in this research. The results showed that out of 16 million tons domestic demand for iron, more than half came from imports. Regarding the role of the steel industry in supporting the defense industry, it can be concluded that the contribution of domestic steel products is very small and has not been able to fully support the defense industry, because there are still many types of steel that must be imported to meet the needs for raw materials for the defense equipment. The 2010 Input-Output Table also shows that the value of domestic steel products used as raw material by the domestic weapons, ammunition, and metallurgy industries was only around IDR. 247.44 billion or only 0.14% of the total domestic use of steel.